Epidemiological changes in tuberculosis and genotyping characteristics of Mycobacterium Tuberculosis in Ningxia, China - Guangtian Liu; Jufen Lv; Linlin Chen; Yinglong Ma; Bofei Liu; Xuefeng Jiang (Frontiers in Microbiology)
IntroductionChina is one of the three countries with the largest TB burden globally, with an increased number of patients reported in 2021.ObjectiveIn this study, we aimed to investigate the epidemiological profile of tuberculosis (TB) and the genotype characteristics of Mycobacterium tuberculosis (MTB) in the Ningxia Hui Autonomous Region, China.MethodsFrom 2005 to 2023, to provide a scientific basis for the precise prevention and control of TB. Epidemiological data on TB in Ningxia were obtained from the China Disease Control and Prevention Information System from 2005 to 2023. The temporal trend of TB incidence was assessed using a Joinpoint regression analysis (Joinpoint 5.2.0), and spatial autocorrelation analyses were performed using ArcGIS 10.8. Spoligotyping and McSpoligotyping based on 222 isolated MTB strains.ResultsFrom 2005 to 2023, 51,345 patients with TB were reported in Ningxia. The incidence of TB decreased from 48.22/100,000 in 2005 to 30.47/100,000 in 2023. Joinpoint analysis showed that the incidence of TB in all age groups exhibited an overall decreasing trend. The incidences were significantly lower among urban residents than among rural residents. A spatial analysis showed that the southern mountainous area had a high incidence, with an average annual incidence of more than 60/100,000 in the Xiji, Lund, and Haiyuan counties, and this showed significant spatial clustering in 2007, 2009, 2014, 2016, and 2018. Genotyping showed that Beijing was the main genotype in Ningxia, accounting for 80.63% of the total (78.26% in 2005–2012 and 83.18% in 2013–2023). A cluster analysis showed that the Beijing type had strong intraregional transmission characteristics. The overall incidence of TB in Ningxia, China, showed a significant downward trend, but the prevalence was high in the southern mountainous regions and rural populations. The high aggregation of Beijing-type genotypes suggests a risk of intra-regional transmission and the need to strengthen surveillance and transmission chain analyses.ConclusionTB incidence in Ningxia declined from 48.22 to 30.47/100,000 (2005–2023), yet remains high in southern mountainous regions. Persistent Beijing-type M. tuberculosis strains dominate, suggesting sustained transmission. Targeted interventions and further molecular studies are needed to enhance control in endemic areas.